A biochemical and lipidomic approach to perceive Halimione portulacoides (L.) response to mercury: An environmental perspective. (January 2023) - Figueira, Etelvina; Matos, Diana; Cardoso, Paulo; Pires, Adília; Fernandes, Célia; Tauler, Romà; Bedia, Carmen
Abstract: The impact of hazardous materials, such as Hg, on life is far from being understood and due to the high number of polluted sites it has generated great concern. A biochemical and lipidomic approach was used to assess the effects of Hg on the saltmarsh halophyte Halimione portulacoides . Plants were collected at two sites of a Hg contaminated saltmarsh. Hg accumulation and distribution in the plant, biochemical parameters (antioxidant and metabolic) and lipid profiles were determined and compared between plant organs and sites (s1 and s2). Hg did not induce antioxidant enzyme activity. Lipid profiles changed under Hg exposure, especially in leaves, decreasing the unsaturation level, the membrane fluidity and stability, and evidencing that membrane lipid remodeling influences plant tolerance to Hg. This knowledge can help select the most appropriate methodologies for the restoration of Hg polluted hotspots, curtailing a serious environmental problem threatening saltmarshes. Highlights: The enzymatic antioxidant mechanisms protecting membranes were not induced. Lipid profile changes lowered membrane saturation and fluidity. Maintaining membranes integrity was essential to tolerate Hg. α-Tocopherol increase protected thylakoid membranes Hg induced more changes in phospholipids, sterols, ceramide and DGDG/MGDG ratio.